2005
DOI: 10.1159/000088900
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Quantitative Detection System for <i>Streptococcus mutans</i> in Saliva Using Monoclonal Antibodies

Abstract: A new semiquantitative enumeration system was developed to detect Streptococcus mutans in saliva. Using species-specific monoclonal antibodies, the system quickly detected salivary S. mutans in 30 min and classified the results into three levels. In this study, saliva samples collected from 28 young adults aged between 22 and 24 years were subjected to the monoclonal antibody-based detecting system and selective medium-based detecting methods. The results generated from the PCR-confirmed culture method indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“… Total microorganisms in saliva: 17 Evaluation was based on three categories of low, middle and high by using the RD test (SHOWA YAKUHIN KAKO, Tokyo, Japan). Lactobacilli in saliva: 18 Dentocult LB (Orion Diagnostica, Espoo, Finland) was used. The level of Lactobacilli was determined as 0: 10 3 /mL or less; 1: 10 4 /mL; 2: 10 5 /mL; and 3: 10 6 /mL or more. Streptococcus mutans in saliva: 19 Level of S. mutans was measured by using SALIVA‐CHECK MUTANS (GC, Tokyo, Japan). The S. mutans level per 1 mL saliva was determined as 1: less than 10 5 /mL; 2: 10 5 /mL; and 3: 10 6 /mL and over. Candida in saliva: 20 Candida was detected and the level measured after cultivation for 4 days using CHROMO Slant Candida Color (KANTO CHEMICAL, Tokyo, Japan). …”
Section: Methodsmentioning
confidence: 99%
“… Total microorganisms in saliva: 17 Evaluation was based on three categories of low, middle and high by using the RD test (SHOWA YAKUHIN KAKO, Tokyo, Japan). Lactobacilli in saliva: 18 Dentocult LB (Orion Diagnostica, Espoo, Finland) was used. The level of Lactobacilli was determined as 0: 10 3 /mL or less; 1: 10 4 /mL; 2: 10 5 /mL; and 3: 10 6 /mL or more. Streptococcus mutans in saliva: 19 Level of S. mutans was measured by using SALIVA‐CHECK MUTANS (GC, Tokyo, Japan). The S. mutans level per 1 mL saliva was determined as 1: less than 10 5 /mL; 2: 10 5 /mL; and 3: 10 6 /mL and over. Candida in saliva: 20 Candida was detected and the level measured after cultivation for 4 days using CHROMO Slant Candida Color (KANTO CHEMICAL, Tokyo, Japan). …”
Section: Methodsmentioning
confidence: 99%
“…The presence of Streptococcus mutans was assessed using a chairside diagnostic kit which has a lower limit of detection of 1 ! 10 4 bacteria/ml [Matsumoto et al, 2006] (Saliva-Check Mutans Test; GC Corporation, Tokyo, Japan). Briefly, all the teeth were swabbed using a sponge-tipped swab supplied by the manufacturer, and the swab saturated with saliva by placing the swab underneath the tongue.…”
Section: Subjectsmentioning
confidence: 99%
“…The method uses monoclonal antibodies specific for S. mutans , and the reaction between the antigen and antibodies can be evaluated after just 15 min. The assay has been analysed in only a few studies ; however, those have shown that the method is useful for determining the number of salivary S. mutans .…”
mentioning
confidence: 99%